SCANDINAVIAN TABLE AND STUBBLE TURNIPS: VARIABILITY AND VALUE FOR BREEDING - D. L. Kornyukhin; A. M. Artemyeva (Овощи России)
The climatic conditions of the Nordic countries are similar to the conditions of the North-West region of the Russian Federation, which makes it possible to introduce interesting varieties for Russian breeding. Most of the local varieties of stubble turnips in the USSR were created using Scandinavian material. Local varieties are the source of the genetic diversity of vegetable crops. The work with such material is promising in terms of searching for sources and donors of valuable traits for breeding programs. 16 samples of local table turnips and stubble turnips from the Scandinavian countries were obtained from the Nordic genebank and a comprehensive study was carried out. Samples are described from the point of view of the existing agrobiological classification of turnip (M.A. Shebalina). Most of the local accessions are mixed populations of two or more types. It was found that the local accessions of Denmark, Norway, Finland and Sweden were represented by table turnips of the Karelian and Petrovsky types, a Tankard yellow type prevailed among the stubble turnips. A representative of a very rare variety type of turnip Kostenevskaya (Petrozavodskaya) was found. The fact of changing of the prevailing types of table and stubble turnips Scandinavian countries is probably connected with the introduction of the widespread European varieties of these cultures. Accessions of local Scandinavian stubble turnips have been identified as sources of productivity and valuable biochemical composition, exceeding the standard variety of Osterzundomsky. Gul Finlandsk, Norway (the Petrovskaya type), Ljusnedal, Sweden (May yellow greenhead type), Rana, Denmark, (the Bortfeld type) and Ova Daehnfeldt, Denmark (Tankard yellow) are promising sources for turnip breeding in Russian Federation.